Entornos Virtuales Aplicados Al Proceso De Enseñanza-Aprendizaje Y Su Incidencia En El Aprendizaje Autónomo Y Colaborativo De Los Estudiantes Del Instituto Tecnológico Superior Babahoyo. - Guevara Albán Gladys (2015)
For the development of this research field investigation, documental and bibliographical was applied with a perspective of analysis and synthesis and by applying statistical surveys and interviews, with all of the above it was reached conclusions and recommendations. We proceeded to implement the proposal made in this investigation achieving test hypotheses raised achieving autonomous and collaborative learning to improve students ITSB.